Transcriptome and metabolome analysis of the responses of salt resistance of different Helianthus annuus germplasms to melatonin - Zhao, Changyan; Liu, Yantao; Jia, Xiuping; Liu, Shengli; Wang, Peng; Zhu, Zhifeng; Wan, Sumei; Duan, Wei (Frontiers in Plant Science, 2025)
IntroductionSalt stress always causes irreversible damages to the growth of Helianthus annuus seedlings in arid and semi-arid areas due to the weakest salt resistance at the seedling stage. Melatonin is a multifunctional molecule that can enhance the salt stress resistance of several crops. However, the effect of melatonin on the salt stress resistance of H. annuus is still unclear.MethodsIn this study, four H. annuus germplasms with different salt resistance (YE988, S2102, Longkuiza 4, and 909S) were selected from a total of 164 germplasms from China, France, Chili, the Unit States, etc. Then, four treatments for the four germplasms were designed, including (1) CK, no salt stress + no melatonin application; (2) MT, no salt stress + melatonin application; (3) K, salt stress + no melatonin application; (4) MK, salt stress + melatonin application. After that, the key genes and metabolic pathways involved in the responses of salt resistance of H. annuus germplasms to melatonin were determined by transcriptome and metabolome analysis.Results and discussionThe results showed that there were 530 differentially expressed genes (37 upregulated genes and 493 down-regulated genes) in H. annuus leaves in MK vs. K, and these genes were mainly involved in fatty acids, diterpenoid biosynthesis, linolenic acid metabolism, cysteine and methionine metabolism. There were 60 differentially abundant metabolites (17 up-regulated metabolites and 43 downregulated metabolites) in leaves in MK vs. K, mainly concentrating in tryptophan metabolism, biosynthesis of amino acids, biosynthesis of secondary metabolites and metabolic pathways. The integrated transcriptome and metabolome analysis results showed that melatonin regulated the b-alanine metabolism, monoterpene biosynthesis, and glutathione metabolism pathways, and increased the contents of spermine and spermidine in cells by promoting the expression of genes such as HannXRQ_Chr07g0195521 and HannXRQ_Chr03g0093321 in the b-alanine metabolic pathway. In summary, melatonin could enhance salt stress signaling by up-regulating the expression of genes related to the synthesis of spermine and spermidine in H. annuus leaves, to regulate photosynthesis and reactive oxygen species metabolism, ultimately enhancing the salt resistance of H. annuus. This study will advance understanding of mechanism by which melatonin enhances salt resistance of H. annuus, and provide a scientific basis for the breeding of saltresistant H. annuus cultivars.